Morphology and fertility status of sperms in frozen Murrah buffalo bull semen upon storage - Singh, Nirmal; Malik, Rakesh; Virmani, Meenakshi; Kennady, Vijayalakshmy; Singh, Pardeep (2020)
The present investigation was undertaken to study the sperm morphology in relation to fertility of frozen semen of Murrah bulls stored for a period of seven months at an organized animal farm in liquid nitrogen can. The semen straws from each bull (N=8) were thawed every month at 37°C for 30 seconds and evaluated for motility, sperm abnormalities, per cent live and dead spermatozoa and per cent intact acrosomes. A total of 126 buffaloes of 2nd to 4th lactation were inseminated with frozen-thawed semen of eight Murrah buffalo bulls during the entire period of investigation, with a total of 12-25 inseminations per bull. Pregnancy diagnosis was done by per-rectal examination after 60-90 days and correlation (P<0.05) of conception rate with progressive sperm motility and live spermatozoa of Murrah buffalo bulls semen was carried out. Significant (P<0.05) positive correlations were obtained between progressive sperm motility, live spermatozoa and conception rate. Thus, it can be concluded that seminal parameters play an important role in determining the fertility of Murrah buffalo bull semen as well as the semen quality is affected by storage under farm conditions due to regular handling.